Policy interventions to address water security impacted by climate change: Adaptation strategies of three case studies across different geographic regions - Quandt, Amy; O'Shea, Bethany; Oke, Saheed; Ololade, Olusola O. (Frontiers in Water, 2022)
Water shortage in terms of both physical and economic water scarcity is still a major issue globally. The looming climate change threat has increased the adverse threats to water security in different regions. However, policy solutions to water security vary in different geographical regions and at different scales (local, regional, national, etc.). Understanding the successes and challenges of different policy solutions is critical to scaling-up successful policies and addressing water security holistically. This paper aims to explore the effects of implementing policies at different scales in three different case study contexts: 1. two Counties in California in the USA, 2. the City of Cape Town in South Africa and 3. the Country of Bangladesh. These case studies highlight various implemented policies and their effectiveness in each context. We reviewed relevant research papers consisting of peer-reviewed journal articles, conference proceedings and grey literature using a content analysis approach based on keywords such as water scarcity, water shortage, climate change, policies, interventions and solutions. Based on this cross-case analysis, we present key strategies moving forward, including: reallocation of water based on different community and sector needs, the importance of stakeholders engagement and public awareness, and a need to implement both short time and long time management plans. There is no one-size fits all policy solution to water scarcity. Understanding the context, scale, and cultural environment will be a key to future water security-focused interventions and policies.